(untitled) (Ágora de Heterodoxias, 2019)
The relationship between school performance and the use of the Moodle platform at the Cibertec Institute were determined in an institution located in Lima, Peru, which offers higher education with 24 professional careers. This institute has the Working Student program in five professional careers, 40% offered online. A cross-sectional correlation design was used, considering a sample of 46 students, in the academic period 2017-II, with the variables: academic performance and four variables related to the Moodle platform: platform use, content management, communication level and level of evaluation of the teaching received. These variables were measured on the ordinal scale with low, regular and high (or frequent) modalities. Spearman correlation and Multiple Correspondence Analysis were used, too. The results corroborate that academic performance is positively and significantly related to the variables: use of the Moodle platform, content management and level of assessment of the teaching methodology, as reported by previous studies, but does not correlate with the level of communication, that was not consistent with previous findings. The results confirm the need to move from the traditional teaching model to a student-centered model, as proposed by the constructivist theory of learning and promoted by several institutions, among which UNESCO, that stands out as a solution to improve the quality of education in developing countries.